Encountering the secular : philosophical endeavors in religion and culture - Atchley, J. Heath, 1973- (Studies in religion and culture (Charlottesville, Va.), 2009)
The author challenges the breach between the secular and the religious, rendering that breach ambiguous. Such ambiguity, the author affirms, is relevant to a time when rigid and simplistic notions of religion and secularity are used to justify thoughtlessness and even violence. All too often the secular is thought of either as a triumph in "overcoming" the presumed irrationality and oppression of religion, or as lament in "losing" the meaning religion is thought once to have offered. Atchley suggests a view of the secular as an opportunity to experience an immanent value that is neither controlled by the human self nor conferred by a divine entity.